Childfree dalam perspektif Agama Islam: analisis persepsi mahasiswa - Aliyyah, Dza Himmatin; Nur Faizin; Adiska Rahma Maulidia; Ahmad Fadhli Fatonia; Fransisca Puspita Wardania (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
Childfree has become a phenomenon that has just been discussed in Indonesia after one of the influencers from Indonesia who lives in Germany named Gita Savitri gave a statement doing childfree, as well as a controversial opinion so that it became a trending topic on Twitter around the end of January to early February 2023. The term childfree refers to someone who has no desire to have children. This study aims to find out the opinions of various scholars about childfree law in Islam and the opinions of S1 students at State University of Malang as the most active academic group in using social media. This study used quantitative methods and literature reviews using references from journals and articles discussing childfree issues that are currently being discussed in Indonesia and using questionnaires with a population of all students in all universities in Indonesia, with a total of 64 respondents. The questionnaire was disseminated through social media platforms, namely WhatsApp.The results of this study stated that the majority of Ulema forbid. The majority of students are aware of the issue of childfree, but do not plan to do and support childfree. This proves that student decisions tend to be positively correlated with the opinions of scholars regarding childfree.